Fetal to Neonatal Heart Rate Transition during Normal Vaginal Deliveries: A Prospective Observational Study - Yuda Munyaw; Jarle Urdal; Hege Ersdal; Matilda Ngarina; Robert Moshiro; Ladislaus Blacy; Jorgen E. Linde (MDPI AG, 2023)
Documentation of fetal to neonatal heart rate (HR) transition is limited. The aim of the current study was to describe HR changes from one hour before to one hour after normal vaginal deliveries. We conducted a prospective observational cohort study in Tanzania from 1 October 2020 to 30 August 2021, including normal vaginal deliveries with normal neonatal outcomes. HR was continuously recorded from one hour before to one hour after delivery, using the Moyo fetal HR meter, NeoBeat newborn HR meter, and the Liveborn Application for data storage. The median, 25th, and 75th HR percentiles were constructed. Overall, 305 deliveries were included. Median (interquartile range; IQR) gestational age was 39 (38-40) weeks and birthweight was 3200 (3000-3500) grams. HR decreased slightly during the last 60 min before delivery from 136 (123,145) to 132 (112,143) beats/minute. After delivery, HR increased within one minute to 168 (143,183) beats/min, before decreasing to around 136 (127,149) beats/min at 60 min after delivery. The drop in HR in the last hour of delivery reflects strong contractions and pushing. The rapid increase in initial neonatal HR reflects an effort to establish spontaneous breathing.